Law Enforcement of the Crime of Embezzlement of Land Certificates, Case Study of the Bali High Prosecutor's Office - Dewi, Ni Kadek Fany Puspita; Wiratny, Ni Ketut; Damanik, Siti Nurmawan (International Journal of Social Service and Research, 2025)
This research is entitled "Law Enforcement of the Crime of Embezzlement of Land Certificates". The background of this research is based on the importance of the Prosecutor's Office in law enforcement of the crime of embezzlement. In practice, law enforcement of embezzlement is often constrained by administrative and coordinating aspects, which affect the enforcement of embezzlement. The type of research used is empirical juridical , which is a legal research method that uses empirical facts taken from human behavior, both verbal behavior obtained from interviews and real behavior carried out through direct observation. The results of the research obtained are that the Handling of Land Certificate Embezzlement Crimes at the Bali High Prosecutor's Office has not been effectively implemented, based on data on the handling of land certificate embezzlement at the Bali High Prosecutor's Office from 2023 to June 2025, Obstacles in Handling Land Certificate Embezzlement Crimes are lack of communication between law enforcement officials, lack of professionalism from the public prosecutor and lack of awareness and public knowledge of land documents and certificates.